VERBAL-LINGUISTICS INTELLIGENCE TOWARDS STUDENT’S SPEAKING ENGLISH SKILLS USING DIGITAL MEDIA (AUDIO VISUAL) IN THE CLASSROOM - Sofa Intan Sutarso Setyaningsih; Andi Hamzah Fansury; Maulina Maulina (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Most Indonesian students have a problem speaking English as their foreign language. Most researchers agreed that it is generally caused by the verbal-linguistic Intelligence of the students. This study aims to determine whether there is a relationship between students’ verbal – linguistic intelligence in their ability to speak English using digital media (audio visual) in classroom. The researcher used a systematic literature review (SLR) for the methodology of the study. Ten articles were presented to collect the data related to students’ verbal – linguistic intelligences and speaking skills. This study finds that students verbal – linguistic intelligence is an internal factor that has to be supported by the other internal factors and also some of external factors to determines the mastery of speaking skills